Working Conditions of the cotton gin: Kondisi kerja Gin kapas - Ismoilov F F (Universitas Muhammadiyah Sidoarjo, 2022)
This comprehensive analysis delves into the various stages of cotton cultivation, examining their effects on the health of cotton growers. Through meticulous research, the study investigates the main factors influencing agricultural production and their direct influence on the well-being of workers involved in cotton farming. Furthermore, hygienic measures are developed and discussed as crucial safeguards to protect the health of these workers. The findings underscore the pressing need for proactive measures to address the health risks associated with cotton cultivation, providing valuable insights for policymakers, researchers, and stakeholders seeking to enhance the sustainability and welfare of the global cotton industry. Highlights: The study focuses on the health implications of cotton cultivation, examining its impact on the well-being of cotton growers. Hygienic measures are developed and proposed to safeguard the health of workers engaged in cotton farming. The research highlights the importance of proactive interventions to address health risks in the cotton industry, contributing to the sustainability and welfare of cotton growers. Keywords: cotton cultivation, health effects, agricultural production, hygienic measures, worker protection